Pola Produksi Etilen, Respirasi, dan Sifat Sensoris Beberapa Buah Pada Kondisi Udara Terkendali - Jumeri Jumeri; Suhardi Suhardi; Tranggono Tranggono (agriTECH, 1997)
One method to prolong the selflife of fruit is to control the atmosphere at a low temperature. In This research, the composition of the standard atmosphere (CO2 : 02 : N2) was 0,03% : 21% : 78%, and the composition of the control atmosphere of CO2 : 02 : N2 were (0% : 10% : 90%), (0% : 5% : 95%), (5%, 10%, 85%), and (5% : 90%). The research goal was to detect athylene production using a spectometer photoacustic, respiration rate using a respirator, and determine the sensory of fruit. The Fruits used in the research are apple (Mains syvestris Mill.), mangosteen (Garcinia mangostana L.), guava (Psidium guajava), chico (Manilkara Zapota Linn), avocado (Persea americana Mill.), and banana (Musa paradisiaca). The final results of the research suggested that generally fruits in control atmospheres determine ethylene production and respiration rate are lower than standart. The sensory of fruit in the control atmosphere is the same, too. The quality of fruits is the control atmosphere combinated temperature 10°C was better than the standart. The control atmosphere with composition CO2 5%, 02 5%, N2 90% resulted the best quality fruit.